How commodity market effects stock market performance? / Muhammad Syafiq Zainal Abidin - Zainal Abidin, Muhammad Syafiq (2021)
The purpose of this study is to investigate the relationship between commodity market and stock market performance in Malaysia. There are many factors that have an impact on stock market performance. Factors that need to be based on this research include the price movement of crude oil, price movement of crude palm oil, currency exchange, and monetary policy. As a consequence, it can have various fundamental consequences. It is therefore very necessary for any economy to determine the reasons for these ties of stock market performance. The previous survey in Malaysian case study produces mixed results. This research is therefore expected to update existing evidence using the latest data and provide more insight into the relationship between commodity market and stock market performance in Malaysia. This study been using WTI crude oil price as proxy for price movement of crude oil, Malaysia crude palm oil price as proxy for price movement of crude palm oil, exchange rate as proxy for currency exchange, and interest rates as proxy for monetary policy as opposed to FBMKLCI (a proxy for stock market performance). In this analysis, a multiple regression model been used to evaluate the relationship between independent variables and the dependent variable. One country has been chosen as a sample of this research over a span of five years. This is in line with previous research. In line with this development, it was proposed that price of commodity has effect to stimulate the stock market performance.